Risk control for hazards of road maintenance and upgrading works towards social sustainability / Muhammad Fadhli Othman - Othman, Muhamad Fadhli (Universiti Teknologi MARA (UiTM), 2025)
Roads are essential for economic advancement and national development. They are crucial for transportation, linking cities, enabling the movement of commodities and individuals, and promoting social connections. Effective road maintenance guarantees safety, comfort, and accessibility for all users, which is essential for social inclusion and improving quality of life. However, numerous complaints over potholes, irregular surfaces, and overall degradation have led to vehicular damage, disturbed traffic flow, and diminished road safety. Moreover, socioeconomic repercussions like accidents, injuries, fatalities, and financial difficulties intensify the issue, affecting social sustainability and the welfare of construction workers engaged in maintenance projects.